PENGEMBANGAN E-LKPD INTERAKTIF BERBANTUAN LIVEWORKSHEET BERBASIS PENDEKATAN OPEN-ENDED DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA KELAS VIII - Silitonga, Nenti; Purba, Glory Indira Diana (MES: Journal of Mathematics Education and Science, 2024)
This study aims to develop an Interactive E-LKPD (student worksheet) with an Open-Ended approach. The subjects in this study were all students of class VIII-1 SMP Swasta Anugerah Harapan Bangsa. The object of this study is the development product of Interactive E-LKPD assisted by Liveworksheet developed based on the Open-Ended approach. The type of research used is research and development with the ADDIE model: analysis, design, development, implementation, and evaluation. In this study, the instruments used were in the form of creative thinking ability tests and observation sheets to measure the effectiveness, practicality, and validity of the products developed in the form of validation sheets, and student and teacher response questionnaires. The data analysis techniques carried out in this study are divided into two, qualitative and quantitative data analysis. Based on the results of the study, it is concluded that the Interactive E-LKPD based on the Open-Ended Approach has fulfilled the aspects of validity, practicality, and effectiveness. This can be seen from the following data: In the aspect of practicality obtained through student and teacher response questionnaires with student response questionnaire results of 96% and teacher response questionnaire results of 92%. In the effectiveness aspect, classical completeness reached ≥85% and the achievement of learning indicators reached ≥75% achieved by at least 65% of students.